Screening and detection of heterogenous vancomycin intermediate Staphylococcus aureus in Hospital Kuala Lumpur Malaysia, using the glycopeptide resistance detection etest and population analysis profiling - Siti Roszilawati Ramli; Hui-min Neoh; Muhammad Nazri Aziz; Salasawati Hussin (MDPI AG, 2012)
In a 3-month study done in Hospital Kuala Lumpur (HKL), 7 out of 320 methicillin resistant Staphylococcus aureus isolates were confirmed as heterogeneous vancomycin intermediate S. aureus (hVISA) using the glycopeptide resistance detection e-test and population analysis, giving a prevalence rate of 2.19%. This is the first report of hVISA in Malaysia.